2012
DOI: 10.2519/jospt.2012.4280
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Changes in the Size and Shape of the Oropharynx Following Acute Whiplash Injury

Abstract: Up to 50% of those who sustain a whiplash injury from a motor vehicle collision (MVC) transition from acute to chronic pain, 5 which results in a substantial personal and economic burden. 2 The variability of reported symptoms, including neck pain, complaints of dizziness, otological and ocular disturbances, headache, loss of concentration and short-term memory, anxiety, insomnia, and depression, 1,7,26,[30][31][32][33][34][35] can challenge even the most astute clinician. Further complicating the clinical pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…That is why a previous history of trauma to the head and neck (e.g. whiplash injury) should be considered [17]. A genetic predisposition has also been hypothesized [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why a previous history of trauma to the head and neck (e.g. whiplash injury) should be considered [17]. A genetic predisposition has also been hypothesized [16].…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations and interventions include CT brain to exclude subarachnoidal hemorrhage or other causes of headache and lumbar puncture to exclude meningitis [17, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…Agreement between the 2 independent reviewers was high (Kappa=0.67) with disagreements on 5 studies resolved through discussion and consensus with a third author (MH). There were eight studies that appeared to meet the inclusion criteria but did not present adequate data [25][26][27][28][29][30][31][32]. We contacted the authors and three provided the data required [30][31][32].…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…The muscles of the cervical spine include both those that move the neck and the smaller muscles which control swallowing and phonation. Although previous research have indicated that the muscles for swallowing and phonation may also play a role in certain cervical spine pathologies such as whiplash and craniocervical injuries, current MR technology does not possess the resolution to accurately depict these small muscles (Anagnostara et al, ; Elliott et al, ; Elliott et al, ; Goulart et al, ). Therefore this article has focused on the 27 muscles that control cervical spine movements.…”
Section: Introductionmentioning
confidence: 99%